Filtering Sinyal Menggunakan Band Pass Filter - Ayu Novira (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Sound is a signal or wave that propagates with a certain frequency and amplitude through intermediary media that are delivered such as water, air and solid objects. Humans can communicate with other humans with sound. But the sound that is released by humans, musical instruments, or other objects does not always sound clear and good, some of the recorded sound has a lot of noise which makes the sound quality is disturbed and not good. The solution for making sound in an object better and cleaner is filtering. [2]. Filters can be interpreted as a circuit that passes a certain frequency band desired and dampens other frequency bands. Filters are divided into two types, namely analog filters and digital filters. According to the impulse response the digital filter is divided into two, namely the Infinite Impulse Filter (IIR) filter and the Finite Impulse Filter (FIR) filter. In this study a filtering process will be carried out on the sound of the guitar. The filter used is the Band Pass Filter, a filter that can be used to isolate or filter certain frequencies in a particular band or frequency range.